Predicting Factors of Roseola Infantum Infected with Human Herpesvirus 6 from Urinary Tract Infection - Hong-Ryul Ko; Son Moon Shin; Sung Won Park (Korean Society of Pediatric Nephrology, 2016)
Purpose The aim of this study was to compare the clinical and laboratory features of infants with roseola infantum due to human herpesvirus 6 (HHV6) infection and those with urinary tract infection (UTI). Methods We retrospectively reviewed the medical records of children who were hospitalized at Cheil General Hospital and Women's Health Care Center, College of Medicine, Dankook University, and diagnosed as having HHV6 infection or UTI. Results Among the infants admitted between September 2014 and May 2016, 92 (male, 45 and female, 47) were included in the study and divided into a HHV6 infection group (n=50) and a UTI group (n=42). The relative risk of UTI compared with that of HHV6 infection increased with pyuria (P <0.001), increased with leukocytosis (mean white blood cell [WBC] count, 15,048±5,756/mm3 vs 87,916±54,056/mm3; P <0.001), increased with C-reactive protein (CRP) level (4.89±4.85 mg/dL vs 1.04±1.76 mg/dL; P <0.001), and younger age (6.3±3.2 months vs 18.3±12.6 months; P <0.001). The relative risk of HHV6 infection compared with that of UTI increased with fever duration (4.3±1.7 days vs 2.8±1.7 days; P <0.001) and decreased with platelet (PLT) count (373±94×103/mm3 vs 229±90×103/mm3 P < 0.001). No significant differences were found between the HHV6 groups according to the presence or absence of pyuria. Conclusion Pyuria, age, fever duration, WBC count, CRP level, and PLT count were the differentiating factors of HHV6 infection from UTI. However, sterile pyuria can occur in children with HHV6 infection. In the presence of pyuria, CRP level and PLT count were the strong predictors of UTI compared with HHV6.